If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(t + -3) + 8t = 9t + -3 Reorder the terms: -5(-3 + t) + 8t = 9t + -3 (-3 * -5 + t * -5) + 8t = 9t + -3 (15 + -5t) + 8t = 9t + -3 Combine like terms: -5t + 8t = 3t 15 + 3t = 9t + -3 Reorder the terms: 15 + 3t = -3 + 9t Solving 15 + 3t = -3 + 9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-9t' to each side of the equation. 15 + 3t + -9t = -3 + 9t + -9t Combine like terms: 3t + -9t = -6t 15 + -6t = -3 + 9t + -9t Combine like terms: 9t + -9t = 0 15 + -6t = -3 + 0 15 + -6t = -3 Add '-15' to each side of the equation. 15 + -15 + -6t = -3 + -15 Combine like terms: 15 + -15 = 0 0 + -6t = -3 + -15 -6t = -3 + -15 Combine like terms: -3 + -15 = -18 -6t = -18 Divide each side by '-6'. t = 3 Simplifying t = 3
| 18-2x=8-3x | | 0.50x+0.05(18-x)=0.10(63) | | 7x+1+7x=-83 | | 8(4+9x)=7(-2-11x) | | 9+k=1+3k | | 15W+W^2=324 | | (10x-7)=(5x)+(4x+6) | | s=0.48-23.75 | | 53=91-c | | 15W*W^2=324 | | (4w-5)=(6w+4) | | =(2a)EXP(3)+(2a+4)(3aEXP(2)-3) | | -2(t+4)+6t=7t-1 | | (5*0.6)+x=6.9 | | 0.8*(8-4)=x | | 3x^2+42x-147=-186 | | k-(-31)=24 | | -2(t+1)+6t=9t-4 | | -35=6b+1 | | 2xy+y-3xy= | | 1.3*x=11.7 | | x-6=-1+4 | | 8c+5c= | | 4p^2q^3+3p^2q=0 | | 7x+7+4x=-125 | | 4m-3(6+2m)=30 | | 5+5(w+4)+w= | | 0.40x+0.40(20)=0.20(130) | | 7x-15x= | | 8+6(x-7)=10-8(x-9) | | 7x+2=-2+3x+16 | | -a^2-a=0 |